Factors Affecting MSMEs' Interest In Using Sharia Crowdfunding Mediated By Perception - Putra, Gilang Kharisma; Apriliyanto, Nanang (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This study aims to analyze the influence of Sharia compliance, subjective norms, and knowledge on the interest of MSME actors in using Sharia crowdfunding mediated by perception. This study uses a quantitative approach with a population of 155,696 MSMEs in Kendal Regency. Sampling used a purposive sampling method with specific criteria, so a sample size of 97 MSME actors was obtained. The data source uses primary data obtained from questionnaires distributed via Google Forms. The study results indicate that Sharia compliance, subjective norms, and knowledge positively affect the interest of MSME actors in using Sharia crowdfunding. Sharia compliance and subjective norms have a positive effect on perception. However, knowledge does not affect perception. Then, perception cannot mediate the relationship between Sharia compliance, subjective norms, and knowledge with the interest of MSME actors in using Sharia crowdfunding. This study can provide insight into the relationship between Sharia compliance, subjective norms, and knowledge with interest and perception. This research can be a reference for future research and for Islamic financial institutions to increase the interest of MSMEs in using Islamic crowdfunding. It can also be more extensive in campaigning against usury, especially for MSME actors.